Setco Automotive Ltd : drivers of a successful turnaround - Desai, Naman, (SAGE Business. Cases., 2019)
The case provides an opportunity for the participants to identify the causes of the operational and financial troubles facing an auto component firm and come up with alternative financial rehabilitation strategies to capitalise on the prospective business environment. The case offers the participants ample opportunities to: (a) prepare the pro-forma financial statements of the firm based on a given set of operating forecasts, (b) determine the optimal capital structure for a firm in the automotive component industry through a detailed financial and business analysis, (c) determine the optimal financial package for the rehabilitation of the firm, and (e) identify and value options to negotiate with stakeholders for the rehabilitation package.